OBESITY IS ASSOCIATED WITH HYPERTENSION IN ADOLESCENTS - Hendy, Hendy; Lanang Sidiartha, I Gusti; Putu Nilawati, Gusti Ayu (Medicina; Vol 44 No 3 (2013): September 2013, 2014)
Obesity has become a global issue. Previous studies in Bali reveal an increase in the proportion of obesity in adolescents. Obesity causes hypertension; hence there should also be an increase in the prevalence of hypertension as well in Bali. Hypertension in obese adolescents could be caused by various factors, hence identification of the risks factors is crucial as a preventive approach. The aim of this study was to prove an association between obesity and hypertension in adolescents, and to look for the risk factors. We used an analitical cross sectional design conducted to 12-14 years old samples. We took body weight, height, waist circumference, hip circumference, and blood pressure measurements with appropriate devices and asked for information regarding life style and familial history by a questionnare filled in by the samples. The association of obese adolescents with hypertension and their risk factors was analyzed by Chi-square and multivariate tests. A total of 225 subjects from Santo Yoseph junior high school students, west Denpasar, Bali, met the inclusion criteria. The proportion of obese subjects in this study was 25.7%. We found that proportion in familial history of obesity was greater in obese than non-obese subjects (70.7 % vs 41.3%). Logistic regression test revealed that obese subjects with hypertension had a body mass index (BMI) > 30 with odds ratio of 7.3 (CI 95% = 1.8 to 28.8) and P = 0.005. We concluded that there was an association between obesity and adolescents with hypertension, and BMI > 30 could be a risk factor for obese adolescents with hypertension.
Keywords: adolescence, obesity, hipertension, BMI